Influence, new and expanded eaudiobook The psychology of persuasion. - Cialdini, Robert B. (2021)
The foundational and wildly popular go-to resource for influence and persuasion—a renowned international bestseller, with over 5 million copies sold—now revised adding: new research, new insights, new examples, and online applications. In the new edition of this highly acclaimed bestseller, Robert Cialdini—New York Times bestselling author of Pre-Suasion and the seminal expert in the fields of influence and persuasion—explains the psychology of why people say yes and how to apply these insights ethically in business and everyday settings. Using memorable stories and relatable examples, Cialdini makes this crucially important subject surprisingly easy. With Cialdini as a guide, you don't have to be a scientist to learn how to use this science. You'll learn Cialdini's Universal Principles of Influence, including new research and new uses so you can become an even more skilled persuader—and just as importantly, you'll learn how to defend yourself against unethical influence attempts. You may think you know these principles, but without understanding their intricacies, you may be ceding their power to someone else. Cialdini's Principles of Persuasion: Reciprocation Commitment and Consistency Social Proof Liking Authority Scarcity Unity, the newest principle for this edition Understanding and applying the principles ethically is cost-free and deceptively easy. Backed by Dr. Cialdini's 35 years of evidence-based, peer-reviewed scientific research—including a three-year field study on what leads people to change—Influence is a comprehensive guide to using these principles to move others in your direction. Supplemental enhancement PDF accompanies the audiobook.